Mechanical properties of silica fume modified high-volume fly ash rubberized self-compacting concrete - Alaloul, W.S. (MDPI AG, 2021)
The existing form of self-compacting concrete (SCC) comprises of a large amount of powdered and fine materials. In this study, a part of the cementitious material was replaced with constant high-volume fly ash, and a portion of fine aggregates was substituted by crumb rubber (CR). Besides that, silica fume (SF) was added, with the hope that by implementing a new type of nanomaterial, the loss in mechanical strength due to previous modifications such as rubberization and replacement will be prevented. Two variables were found to influence the constituent/component in the mix design: SF and CR. The proportion of SF varies from 0 to 10, while that of CR from 0 to 30 by volume of the total river sand, where 55 of cement was replaced by the fly ash. A total of 13 rubberized SCC samples with CR and SF as controlling variables were made, and their design mix was produced by a Design of Experiment (DOE) under the Response Surface Methodology (RSM). The results reveal a slight increase in the mechanical properties with the addition of SF. The theoretical mathematical models and equation for each different mechanical strength were also developed after incorporating the experimental results into the software. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.